Algorithmic transparency and perceived organizational justice in fostering employee trust - Yusmedi Nurfaizal; Mugiarti; Agapito Barros (Jurnal Manajemen dan Pemasaran Jasa, 2026)
This study examines the effects of algorithmic transparency and employees’ perceived organizational justice on employee trust in algorithmically managed work environments, with psychological safety as a mediating variable and digital literacy as a moderating factor. Drawing on socio-technical and organizational behavior perspectives, eight hypotheses were proposed and empirically tested. Data were collected from non-freelance employees working in two platform-based logistics companies, Shopee Express and J&T Express, operating in Banyumas Regency, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that algorithmic transparency and perceived organizational justice have significant positive effects on employee trust, both directly and indirectly through psychological safety. In addition, digital literacy strengthens the positive relationship between psychological safety and employee trust. These findings underscore the importance of integrating transparent algorithmic systems, perceived fairness in organizational practices, and employees’ psychological readiness in building trust within algorithm-driven organizations. The study contributes to the literature by positioning psychological safety as a key affective mechanism linking algorithmic management practices to trust, while extending empirical evidence through an industry-based, multi-firm analysis within the platform logistics sector.